Analysis of Voice Onset Time in English Pronunciation by Teenagers: An Acoustic Phonetic Study - Prima sholihatun; T Syarfina; Mahriyuni (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This research aims to investigate the acoustic characteristics of English pronunciation by teenagers through the Voice Onset Time (VOT) parameter. Specifically, the research emphasizes the analysis of VOT duration in initial plosive consonants [p], [b], [t], [d], [k], and [g] in English. The study employs a quantitative approach with an experimental method. Data were collected through recordings of words containing plosive consonants spoken by several teenagers. The recordings were then digitized into sound wave format and analyzed using Praat software through stages of digitization, data segmentation, and contour replication. This approach enables accurate measurement of VOT values for plosive consonants. The VOT analysis results indicate significant variations between individuals. The average VOT values for voiceless consonants [p], [t], and [k] are 46 ms, 82 ms, and 49 ms, respectively, while voiced consonants [b], [d], and [g] have average VOT values of 38 ms, -13 ms, and 10 ms, respectively. These findings suggest that the students tend to produce voiceless consonants with shorter VOT durations compared to native speakers, making them sound closer to voiced consonants.